ISLAMIC CORPORATE SOCIAL RESPONSIBILITY MEASUREMENT MODEL IN IMPROVING FINANCIAL PERFORMANCE FOR ISLAMIC BANKING - Elizar Sinambela; Fitriani Saragih; M.Firza Alpi (International Journal of Accounting, Finance and Business, 2020)
This study aims to determine the disclosure model Islamic measurement of Corporate Social Responsibility and its influence in improving financial performance in the Islamic Banking in Medan. This research is motivated by the development of Islamic banking is currently impacting the financial performance of each company and their obligation to disclose corporate social responsibility. Implementation of corporate social responsibility are believed to increase the company's financial performance, which investors tend to invest in companies that perform corporate social responsibility activities. But in Islamic banking data show financial performance and disclosure of Islamic Corporate Social Responsibility (ICSR) is still low because under the number one (1).Based on the survey results revealed that the low value of ICSR caused by Islamic banking has yet to reveal all its social responsibilities. Especially on sharia-based component. Likewise, the acquisition value of a low ROE is because Islamic banking is not maximized in managing equity they have. This condition is also supported by the results of the regression test where the results showed the influence of disclosureIslamic Corporate Social Responsibility(ICSR) of the Financial Performance as measured by ROE. The result is expected to be a reference for Islamic banking is there to dodisclosure model measurement Islamic Corporate Social Responsibility (ICSR) so as to improve the overall financial performance of Islamic banking both in Indonesia and in the world.